Development and sensory acceptance of products manufactured with green banana flour (Research, Society and Development, 2022)
The present work aimed to develop, to make sensory evaluation and to investigate the purchase intention of bakery products based on green banana flour. This is a descriptive study of a qualitative-quantitative approach, in which three different products (bread, cookie and cake) based on green banana flour, were tested through sensory assessment. Statistical data analysis was used to analyze the results, at a significance level of 5%. It was observed that all sensory attributes (appearance, aroma, texture and taste) showed a significant correlation among themselves and the results revealed that there was a difference between the three range of products evaluated, in relation to each of the attributes. The cookie was the one that had a higher acceptance of all its attributes when compared to bread and cake. According to purchase intention, the best acceptance was also to the cookie, followed by bread and cake. Considering the results obtained in the present study, it can be stated that cookie and cake made with green banana flour were well accepted by the judges and could be considered products well received by consumers. For these three products tested no other types of flour were necessary.